1989
DOI: 10.1002/bjs.1800760919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-invasive and invasive methods in the assessment of short saphenous vein termination

Abstract: Surgery of the short saphenous vein is associated with a high recurrence rate because of variations in the anatomy or inadequate clinical examination. To prevent this, accurate definition of the pattern and level of termination of the saphenopopliteal junction and flush ligation is necessary. Clinical examination, Doppler ultrasound, duplex scanning and peroperative venography have been compared to assess the level of termination of the short saphenous vein. In all, 64 limbs of 46 patients were examined. In 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 7 publications
1
42
1
2
Order By: Relevance
“…6 Most UK vascular surgeons (89% in a recent questionnaire study) employ routine diagnostic imaging before SSV surgery because of the difficulty assessing this area by hand-held Doppler, and the variable anatomy of veins in the popliteal fossa. 7,8 Preoperative duplex marking of the SPJ was done selectively, according to the result of the diagnostic scan by surgeons in the present study, as mirrored by national data. 9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Most UK vascular surgeons (89% in a recent questionnaire study) employ routine diagnostic imaging before SSV surgery because of the difficulty assessing this area by hand-held Doppler, and the variable anatomy of veins in the popliteal fossa. 7,8 Preoperative duplex marking of the SPJ was done selectively, according to the result of the diagnostic scan by surgeons in the present study, as mirrored by national data. 9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Where the vascular technologist is able to obtain a good view at duplex scanning, it has been found that the duplex results closely mirror the peroperative situation. Also in the assessment of recurrent varicosities of the SSV, colour-coded duplex examination of the SPJ was reported to have an accuracy ranging between 96 and 100% [25,26].…”
Section: Mthsmentioning
confidence: 99%
“…This affected 5% of the limbs with primary varicose veins and 10% of the limbs with recurrent varicose veins after previous greater saphenous surgery. Other studies also reported that the prevalence of reflux in the VG ranged from 2% to 19% (6, 19-22). However, we could not evaluate the prevalence of VG among all patients who underwent Doppler US because we only evaluated the incidence of an incompetent VG.…”
Section: Discussionmentioning
confidence: 90%